Mendalami Ketuhanan Yang Maha Esa: Analisis Tauhid dalam Konteks Sejarah dan Perjuangan - Arlis; Yecki Bus; Eskarni Ushalli; Neni Yuherlis (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2024)
This article examines the concept of Tauhid (Islamic monotheism) as a foundational principle in Indonesia's struggle for independence and its subsequent nation-building efforts. Tauhid emphasizes the unity of God and serves as a unifying force among diverse ethnic and religious communities in Indonesia. The discussion traces how Tauhid influenced the early nationalist movements, where Islamic scholars and leaders played crucial roles in advocating for independence based on religious principles of justice, equality, and human dignity. Post-independence, the ideology of Pancasila—promoting unity amidst diversity—incorporated elements of Tauhid, fostering a national identity that respects religious pluralism while upholding shared ethical values. This paper argues that understanding Tauhid provides insights into Indonesia's unique path to nationhood, illustrating how religious principles can contribute to social cohesion and national unity. By exploring Tauhid's role in shaping Indonesia's history and identity, this study contributes to broader discussions on the intersection of religion, nationalism, and governance in diverse societies.